Pregnant Patients with COVID-19 Admitted to an ICU: A Comparison with a Historical Cohort of Critical Pregnant Patients without COVID-19 - Carmine Iacovazzo; Letizia Capasso; Carola Visani; Serena Salomè; Maria Vargas (Life, 2024)
Aim of the study: Maternal mortality and ICU admissions have increased during the COVID-19 pandemic. We reported a case-series of pregnant patients with COVID-19 admitted to an ICU and we compared them with a historical cohort of pregnant patients admitted to an ICU without COVID-19. Methods: We included all pregnant patients with laboratory-confirmed COVID-19 infection admitted to our ICU in 2021. As a historical control group, we included all pregnant women who were admitted to our ICU between 1 January 2008 and 31 December 2013. Results: In 2021, 11 pregnant patients (pts) with COVID-19 were admitted to an ICU, representing 2.87% of ICU admissions. We found that pregnant patients with COVID-19 (1) had a higher BMI (34.6 vs. 28.8, p = 0.04) and a lower gestational age (30.6 vs. 34 weeks, p = 0.03), (2) were mainly admitted for respiratory failure (100% vs. 2.7%; p = 0.001) and (3) required more days of invasive and non-invasive ventilations (54.5% vs. 5.2%, p = 0.002), a longer duration of stay at the ICU (21.9 vs. 4.8 days, p < 0.0001) and had a higher mortality rate (27.3% vs. 0%, p = 0.0192). Conclusions: Pregnant patients with COVID-19 represent a challenge for ICU physicians due to their different characteristics and outcomes when compared to pregnant patients without COVID-19.